Ca2+ regulation of paracellular permeability in the middle intestine of the eel, Anguilla anguilla. - TRISCHITTA F; DENARO M. G; FAGGIO C; LIONETTO, Maria Giulia (Journal of Comparative Physiology B: Biochemical, Systemic, and Environmental Physiology, 2001)
The role of Ca++ on the regulation of the paracellular pathway permeability of the middle intestine of Anguilla anguilla was studied by measuring the transepithelial resistance and the dilution potential, generated when one half of NaCl in the mucosal solution was substituted iso-osmotically with mannitol, in various experimental conditions altering extracellular and/or intracellular calcium levels. We found that removal of Ca++ in the presence of ethylene glycol-bis(β-aminoethyl ether) (EGTA) from both the mucosal and the serosal side, but not from one side only, reduced both the transepithelial resistance and the magnitude of the dilution potential. The irreversibility of this effect suggests a destruction of the organization of the junction in the nominal absence of Ca++. However a modulatory role of extracellular Ca++ cannot be excluded. The decrease of the intracellular Ca++ activity, produced by using verapamil to block the Ca++ entry into the cell, or by adding 3,4,5-trimethoxybenzoic acid 8-(diethylamino) octyl ester (hydrochloride) (TMB-8), an inhibitor of Ca++ release from the intracellular stores, reduced both the transepithelial resistance and the magnitude of the dilution potential, indicating a role of cytosolic Ca++ in the modulation of the paracellular permeability. However the rise of calcium activity produced by the Ca++ ionophore calcimycin (A23187) evoked an identical effect, suggesting that any change in physiological intracellular Ca++ activity alters the paracellular permeability.